Penerapan Prinsip Strict Liability dalam Kasus Tumpahan Limbah B3 di Kabupaten Bekasi, Jawa Barat - Mahyzta Karindradevi; Mochamat Syaifudin Ayub; Naila Amelia Putri; Nur Laili Dyani Agustina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the causes and impacts of hazardous and toxic waste (B3) spills in Bekasi Regency, West Java. B3 waste such as used oil, batteries, and heavy metals can pollute the environment and harm public health. Key causes include lack of treatment facilities, violations of disposal procedures, and weather factors like flooding. The research uses normative legal approaches. The findings of this study underscore the necessity of managing hazardous waste in compliance with established regulations, enforcing environmental laws rigorously, and ensuring active involvement from both government institutions and the public in monitoring efforts. The application of the strict liability principle is considered highly important in providing a deterrent effect against polluters through legal accountability.